2014
DOI: 10.1186/2049-2618-2-29
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory tract clinical sample selection for microbiota analysis in patients with pulmonary tuberculosis

Abstract: BackgroundChanges in respiratory tract microbiota have been associated with diseases such as tuberculosis, a global public health problem that affects millions of people each year. This pilot study was carried out using sputum, oropharynx, and nasal respiratory tract samples collected from patients with pulmonary tuberculosis and healthy control individuals, in order to compare sample types and their usefulness in assessing changes in bacterial and fungal communities.FindingsMost V1-V2 16S rRNA gene sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 23 publications
8
53
0
Order By: Relevance
“…This study also demonstrated that “nasal” clusters separate from “Sputum” and “Oropharynx”, a finding that has been confirmed very recently by another group (Bassis CM, 2015). This group additionally reported on the presence of fungi in the TB lung, with members of the phylum Ascomycota dominating (Botero, et al, 2014). When comparing the sputum to the oropharynx, this group did not note a difference, a finding likely due to contamination during sputum expectoration.…”
Section: Lung Microbiome In Pulmonary Tbmentioning
confidence: 98%
See 2 more Smart Citations
“…This study also demonstrated that “nasal” clusters separate from “Sputum” and “Oropharynx”, a finding that has been confirmed very recently by another group (Bassis CM, 2015). This group additionally reported on the presence of fungi in the TB lung, with members of the phylum Ascomycota dominating (Botero, et al, 2014). When comparing the sputum to the oropharynx, this group did not note a difference, a finding likely due to contamination during sputum expectoration.…”
Section: Lung Microbiome In Pulmonary Tbmentioning
confidence: 98%
“…However, they also reported finding Fusobacteria and determined that Proteobacteria and Bacteroidetes were the dominant organisms in TB, with Firmicutes predominantly in control lungs (Cheung et al, 2013). A study published last year which unfortunately did not compare TB sputum to healthy sputum nonetheless noted that Bacteroidetes, Fusobacteria, and Actinobacteria were dominant in TB (Botero et al, 2014). This study also demonstrated that “nasal” clusters separate from “Sputum” and “Oropharynx”, a finding that has been confirmed very recently by another group (Bassis CM, 2015).…”
Section: Lung Microbiome In Pulmonary Tbmentioning
confidence: 99%
See 1 more Smart Citation
“…16S rRNA gene-based profiling techniques are widely used for deciphering the structure of bacterial communities residing in varied ecological niches (Gill et al, 2006;Huse et al, 2012;Yatsunenko et al, 2012). In the context of clinical studies, a (cross-sectional/ longitudinal) comparison of community structures between the two or more states of health/ disease can help in preliminary identification of specific bacterial taxa (or groups of taxa) that demonstrate statistically significant association(s) between their presence (or abundance) and the state of health/ disease severity (Alekseyenko et al, 2013;Botero et al, 2014;Cui et al, 2012;Ganju et al, 2016;Griffen et al, 2012; Kirst et al, 2015;Tandon et al, 2018). In some cases, differences in community structure (quantified using alpha or beta diversity measures) of the studied microbial communities have also served as important cues to understand dynamics of specific clinical conditions (Haque et al, 2017;Tandon et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…12,13 TB AND THE MICROBIOME In this review, eight studies examined the association between pulmonary TB infection and disease and the microbiome, including an animal study, 30 a case report, 31 and 6 case-control studies (Table 1). 21,[32][33][34][35][36] Key study findings are highlighted in the following two sections (regarding TB and the gut or lung microbiome, respectively), and study methodology is compared in the third section.…”
Section: Introductionmentioning
confidence: 99%